2020
DOI: 10.3390/cancers12123599
|View full text |Cite
|
Sign up to set email alerts
|

Potential Roles of Tumor Cell- and Stroma Cell-Derived Small Extracellular Vesicles in Promoting a Pro-Angiogenic Tumor Microenvironment

Abstract: Extracellular vesicles (EVs) are produced and released by all cells and are present in all body fluids. They exist in a variety of sizes, however, small extracellular vesicles (sEVs), the EV subset with a size range from 30 to 150 nm, are of current interest. They are characterized by a distinct biogenesis and complex cargo composition, which reflects the cytosolic contents and cell-surface molecules of the parent cells. This cargo consists of proteins, nucleic acids, and lipids and is competent in inducing si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 90 publications
(149 reference statements)
0
23
0
Order By: Relevance
“…Compared to genetic or immune prognostic markers, TSR could be obtained by conventional pathological analysis with a microscope, which is simple, inexpensive, effective, and feasible in real-world clinical practice [ 35 ]. Moreover, treatments targeting tumour stroma and other components of tumor microenvironment may be effective and promising [ 36 , 37 ]. Once therapy targeting tumor stroma becomes critical, measuring of TSR may be helpful to identify patients with optimal therapy response in patients with NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to genetic or immune prognostic markers, TSR could be obtained by conventional pathological analysis with a microscope, which is simple, inexpensive, effective, and feasible in real-world clinical practice [ 35 ]. Moreover, treatments targeting tumour stroma and other components of tumor microenvironment may be effective and promising [ 36 , 37 ]. Once therapy targeting tumor stroma becomes critical, measuring of TSR may be helpful to identify patients with optimal therapy response in patients with NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…As the long-term stimulation of diabetes itself, the activation of PKC and other factors, promote the synthesis of PDGF is promoted to, increases the level of PDGF in the retina and kidney of diabetic patients, further advance the formation of new blood vessels by stimulating intercellular adhesion molecule -1 (IGAM-1) and other ways, and aggravate microvascular-related lesions. The tumor microenvironment also contains abundant PDGF, possibly for the following reasons: TAMs 32,49,50,63 and CAFs 31,46 can secrete PDGF, and on the other hand, active HIF-1 can increase the release of PDGF under hypoxia conditions. 35 PDGF promotes tumor angiogenesis through its effects and co-action with other factors, 8 but overexpression of PDGF-B significantly inhibits tumor growth in vivo.…”
Section: Pdgfmentioning
confidence: 99%
“…TAMs are a large family of macrophages 49 and are the most abundant population of tumor-infiltrating immune cells in TME. 29,49,63 M1 or M2 macrophages are induced by Th1 and Th2 cytokines, respectively, are the two main cell subtypes of TAMs. Moreover, the two effects are opposite: M1 macrophages are mainly involved in killing tumor cells, while M2 macrophages can promote angiogenesis.…”
Section: Tamsmentioning
confidence: 99%
“…Since the role of ADO as a contributor to tumor progression has been recognized in recent years, numerous pre-clinical and clinical studies utilizing pharmacologic inhibitors, siRNA or antibodies specific for the components of the adenosine pathway and antagonists of adenosine receptors have been conducted (reviewed in [ 40 , 41 , 42 ]). Pre-clinical studies in various in vitro and in vivo tumor models have shown efficacy and are currently entering the clinical arena [ 25 , 43 , 44 ].…”
Section: Significance Of the Tex-mediated Adenosinergic Pathwaymentioning
confidence: 99%